2019
DOI: 10.1016/j.psicoe.2018.07.002
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of a Psycho-educational App to Reduce Sexist Attitudes in Adolescents

Abstract: El presente estudio evalúa la eficacia de una intervención consistente en el uso de una aplicación móvil en formato juego dirigida a reducir el sexismo en adolescentes. Se lleva a cabo un estudio cuasiexperimental pretest-postest con grupos de intervención y de control. Participan 369 estudiantes de Educación Secundaria Obligatoria de entre 12 y 17 años de la provincia de Valencia, de los cuales 196 se asignan a la condición de intervención con la aplicación y 173 al grupo control. Se evalúa sexismo hostil y b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 40 publications
0
13
0
1
Order By: Relevance
“…Wang [ 45 ] observed that as the educational level of participants increased, attitudes and perceptions towards partner violence had no significant effect. In contrast, Navarro-Pérez et al [ 44 ] point out that formal education has a direct influence on sexist attitudes; in the intervention performed, sexism was reduced between 6 and 12%.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Wang [ 45 ] observed that as the educational level of participants increased, attitudes and perceptions towards partner violence had no significant effect. In contrast, Navarro-Pérez et al [ 44 ] point out that formal education has a direct influence on sexist attitudes; in the intervention performed, sexism was reduced between 6 and 12%.…”
Section: Discussionmentioning
confidence: 92%
“…Age was inversely related to the love–abuse link, so that as it increases, the association diminishes. Although the age margin analyzed is narrow, this finding may be indicative of a tendency toward the establishment of healthier romantic relationships as adolescents mature [ 37 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, they suggest that beyond explicit attitudes and behaviors, policy makers should also target subtler manifestations of sexism such as the sexual objectification of women—for example, by teaching about the negative implications for women of receiving objectifying gazes (Saguy et al, 2010) and comments, even if complimentary, about their bodies (Kahalon et al, 2018a). These interventions can be informed by existing strategies to reduce other forms of sexism, which aim to increase sensitivity for sexism in everyday lives (Becker & Swim, 2011), educate about the harm and prevalence of sexist beliefs (Becker & Swim, 2012), and raise awareness to the existence of more elusive and unconscious sexist behaviors (Shields, Zawadzki, & Johnson, 2011; see also Navarro-Pérez, Carbonell, & Oliver, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…It was also discovered that higher learning motivation would result in better effectiveness. Navarro-Pérez et al ( 2019 ) found better performance in students with high learning motivation and better performance in students with intrinsic motivation than in those with extrinsic motivation. Consequently, the following hypotheses are proposed.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%